Changes in the European Union definition for endocrine disruptors: how many molecules remain a cause for concern? The example of crop protection products used in agriculture in France in the six last decades - Roger, Cloé; Paul, Adèle; Fort, Emmanuel; Lamouroux, Céline; Samal, Areejit; Spinosi, Johan; Charbotel, Barbara (Frontiers in Public Health, 2024)
The endocrine disrupting effects of Phytopharmaceutical Active Substances (PAS) on human health are a public health concern. The CIPATOX-PE database, created in 2018, listed the PAS authorized in France between 1961 and 2014 presenting endocrine disrupting effects for humans according to data from official international organizations. Since the creation of CIPATOX-PE, European regulations have changed, new initiatives identifying substances with endocrine disrupting effects have been implemented and new PAS have been licensed.The aim was to update the CIPATOX-PE database by considering new 2018 European endocrine disrupting effect identification criteria, as well as the new PAS authorized on the market in France since 2015.Methods: endocrine disrupting effects assessment of PAS from five international governmental and non-governmental initiatives were reviewed as well as levels of evidence retained by these initiatives for eighteen endocrine target organs.Results: The synthesis of the identified endocrine disrupting effects allowed to assign an endocrine disrupting effect level of concern for 241 PAS among 980 authorized in France between 1961 and 2021.Thus, according to the updated CIPATOX-PE data, 44 PAS (18.3%) had an endocrine disrupting effect classified as "high concern", 133 PAS (55.2%) "concern", and 64 PAS (26.6%) "unknown effect" in the current state of knowledge. 42 PAS with an endocrine disrupting effect of "high concern" are similarly classified in CIPATOX-PE-2018 and 2021, and 2 new PAS were identified as having an endocrine disrupting effect of "high concern" in the update, both previously classified with endocrine disrupting effect of "concern" in CIPATOX-PE-2018. Finally, a PAS was identified as having an Endocrine disrupting effect of "high concern" in CIPATOX-PE-2018, but is now classified as a PAS not investigated for Endocrine disrupting effects in CIPATOX-PE-2021.The Endocrine Target Organs associated with the largest number of PAS with an Endocrine disrupting effect of "high concern" is the reproductive system with 31 PAS. This is followed by the thyroid with 25 PAS and the hypothalamic-pituitary axis (excluding the gonadotropic axis) with 5 PAS.Discussion: The proposed Endocrine disrupting effect indicator, which is not a regulatory classification, can be used as epidemiological tool for occupational risks and surveillance.